2021
DOI: 10.2147/oaem.s309508
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Medication-Related Emergency Department Admissions Among Patients with Cardiovascular Diseases at Mbarara Regional Referral Hospital, South-Western Uganda

Abstract: Background Medication-related emergency department admissions impose a huge and unnecessary burden on the healthcare system. We sought to determine the prevalence and predictors of medication-related emergency department admissions, among patients with cardiovascular diseases at Mbarara Regional Referral Hospital, Uganda. Methods Institutional research ethics approval was secured to conduct a cross-sectional study at the Mbarara Regional Referral Hospital emergency depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 61 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Other studies among admitted elderly patients have reported cardiovascular drugs, nervous system agents and anti-infective agents as the cause of ADRs. 11 , 12 A study in Uganda by Kiguba et al 17 reported herbal medicines to be linked to hospital-acquired ADRs. The Uganda treatment guidelines require that misoprostol is administered from a hospital setting; however, it is a common practice for patients to self-medicate with misoprostol to initiate abortion before seeking professional care which causes adverse events such as incomplete abortion, failed abortion, missed abortion, severe anaemia, haemorrhagic shock, sepsis, ectopic pregnancy and ruptured uterus 26 requiring hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies among admitted elderly patients have reported cardiovascular drugs, nervous system agents and anti-infective agents as the cause of ADRs. 11 , 12 A study in Uganda by Kiguba et al 17 reported herbal medicines to be linked to hospital-acquired ADRs. The Uganda treatment guidelines require that misoprostol is administered from a hospital setting; however, it is a common practice for patients to self-medicate with misoprostol to initiate abortion before seeking professional care which causes adverse events such as incomplete abortion, failed abortion, missed abortion, severe anaemia, haemorrhagic shock, sepsis, ectopic pregnancy and ruptured uterus 26 requiring hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 10 Recent studies in Uganda among the admitted elderly implicate cardiovascular drugs, nervous system agents and anti-infective agents as the common cause of ADRs. 11 , 12 Self-medication has been highlighted to be associated with ADR-related hospitalization in HIC 13 , 14 ; however, such data are scarce in Sub-Saharan Africa (SSA) where self-medication is rampant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations